Réponses

  • Utilisateur Brainly
2014-09-10T17:46:55+02:00
A= 15 + 3 - 6 + 2 - 7
A= 15 + 3 + 2 - 7 - 6
A= 20 - 13
A= 7

B= - 8 + 4 - 5 - 6 +11
B= 4 + 11 - 8 - 6 - 5
B= 15 - 19
B= - 4

C= ( + 10 ) - ( -4 ) + ( - 1 ) + ( + 5 ) - (+9 )
C= 10 + 4 - 1 + 5 - 9
C= 10 + 4 + 5 - 1 - 9
C= 19 - 10
C= 9

D= ( -15 ) - ( +14 ) + ( + 30 ) + ( -15 ) - ( - 20 )
D= - 15 - 14 + 30 - 15 + 20
D= 30 + 20 - 15 - 15 - 14
D= 50 - 44
D= 6
2014-09-10T17:57:08+02:00
A = 15 + 3 - 6 + 2 - 7
= 18 - 4 - 7
= 14 - 7
= 7

B = - 8 + 4 - 5 - 6 +11
= -4 - 11 + 11
= -15 + 11
= -4

C = ( + 10 ) - ( -4 ) + ( - 1 ) + ( + 5 ) - (+9 )
= 14 + 4 - 9
= 18 - 9
= 9

D = ( -15 ) - ( +14 ) + ( + 30 ) + ( -15 ) - ( - 20 )
= -29 + 15 - ( -20 )
= -14 - ( -20 )
= 6